Internet Addiction and Loneliness Among Students of University of Shkodra - Hasmujaj, Elona (European Scientific Journal, ESJ, 2016)
Internet addiction is a kind of consumer behavior that has attracted the attention of many studies. Loneliness is a frequently reported mental illness addicted to the internet. Lonely individuals may be drawn online because of the increased potential for companionship, the changed social interaction patterns online, and as a way to modulate negative moods associated with loneliness. This study examines the relationship between internet addiction and loneliness among albanian students of University of Shkodra and the gender differences to this aspect. The participants to the research were 151 students from 18-23 years old, who live in different places of North Albania. In order to trace the connection between loneliness and Internet addiction among students was used the self-administered questionnaires: Internet Addiction Test (IAT) and UCLA Loneliness Scale. The research has shown that there is a mild negative correlation between loneliness and Internet addiction, on the other hand no gender differences was found in terms of internet addiction and loneliness level. The results suggest that students addicted to the Internet have significantly lower rates of loneliness.